Evaluation of upper extremity anthropometric measurements in terms of sex estimation - Uzun, Özlem; Yeginoğlu, Gülay; Kalkışım, Şahi Nur; Ertemoğlu Öksüz, Canan; Zihni, Nihat Burak (International Journal of Research in Medical Sciences, 2017)
Background: One of the most important and broadest areas of forensic medicine is identification. Among the various parameters used, the most important criterion for identification is to determine the sex of the individual concerned. The aim of the current study was to develop models to determine the sex of subjects in case of forensic situations in which anatomical remains and residues of the upper extremity have to be identified. Methods: The research consisted of university students aged 18-25. Arm, forearm, upper extremity, hand, third finger and palmar length, hand width, wrist width, and wrist circumference measurements from 400 subjects were taken from the right and left upper extremities on the basis of anthropometric points. Models were than developed using logistic regression analysis. Results: The developed models provided valid and reliable sex estimates with high and accuracy rates and low prediction errors. Conclusions: The models are representative for the Turkish population in terms of identification. The study thesis can be regarded as an alternative method when economic or other difficulties are encountered in terms of DNA analysis.